2023
DOI: 10.55677/ijssers/v03i4y2023-08
|View full text |Cite
|
Sign up to set email alerts
|

Teachers and pupils’ perspectives on Teaching and Learning of Geography in selected schools of Luapula and Lusaka provinces of Zambia: Benefits, Challenges and Prospects

Abstract: Geography education in schools plays a critical role in providing pupils with a comprehensive understanding of the world around them. Using descriptive research design, which involved qualitative data collection and analysis, this study explored pupils and teachers’ perspectives on benefits, challenges and prospects of learning and teaching geography in schools. The study used homogenous purposive sampling to select schools and participants for the study. A total of 4 schools were sampled. 8 geography teachers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Murphy (2015) also indicated that students with ADHD could be productive in general education classrooms if educators recognize and employ efficient teaching and behavioral management approaches. Nonetheless, general education classroom teachers from many parts of the world have voiced various concerns about teaching students with ADHD, citing issues such as inadequate training (Mubita & Kalimaposo, 2016) and lack of administrative support (Guerra et al, 2017). Therefore, current research is necessary to learn about teachers' understanding of teaching this population (Schuck et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Murphy (2015) also indicated that students with ADHD could be productive in general education classrooms if educators recognize and employ efficient teaching and behavioral management approaches. Nonetheless, general education classroom teachers from many parts of the world have voiced various concerns about teaching students with ADHD, citing issues such as inadequate training (Mubita & Kalimaposo, 2016) and lack of administrative support (Guerra et al, 2017). Therefore, current research is necessary to learn about teachers' understanding of teaching this population (Schuck et al, 2016).…”
Section: Introductionmentioning
confidence: 99%